The Effect of Work Family Conflict on Turnover Intention with Work Stress as A Variable Mediation - Rianda, Alifa Sindy; Fitria, Yuki (Universitas Negeri Padang, 2023)
The purpose of this study is to analyze work stress as a mediation between work family conflict on turnover intention. The population in this study were all non-PNS nurses at the Central General Hospital. Dr. M. Djamil Padang, totaling 443 nurses. The sampling technique used was proportions stratified random sampling. The number of samples that can be used in this research is 210 respondents. This study was analyzed using Structural Equation Modeling (SEM) with the SmartPLS 3.3.3. The findings from this study are: (1) There is an influence of work family conflict on turnover intention. The work family conflict variable has a positive and significant effect on turnover intention (2) There is an effect of work stress on turnover intention. Work stress variable has a positive and significant effect on turnover intention. (3) There is an influence of work family conflict on work stress. The work family conflict variable has a positive and significant effect on work stress. (4) Work stress is proven to mediate the relationship between work family conflict and turnover intention